Phylogenetic relationships of Mycobacterium tuberculosis isolates in Poland: The emergence of Beijing genotype among multidrug-resistant cases - Bakuła, Zofia; Marczak, Mateusz; Bluszcz, Agata; Proboszcz, Małgorzata; Kościuch, Justyna; Krenke, Rafał; Stakėnas, Petras; Mokrousov, Igor; Jagielski, Tomasz (Frontiers in Cellular and Infection Microbiology, 2023)
Background: The epidemiological situation of tuberculosis (TB) in Poland urges for its continuous and scrupulous monitoring. The objective of this study was to explore the genetic diversity of multidrug-resistant (MDR) and drug-susceptible (DS) Mycobacterium tuberculosis isolates from Poland with a combination of spoligotyping and high-resolution mycobacterial interspersed repetitive unit-variable number tandem repeat (MIRU-VNTR) analysis. The results were placed in the Northern and Eastern Europe context. Methods: The study included 89 (39 MDR and 50 DS) M. tuberculosis isolates collected from as many patients between 2018 and 2021 in Poland. The analysis was done using spoligotyping, and MIRU-VNTR typing at 24 standard loci. The data were compared to those available on Poland and neighbors and global M. tuberculosis datasets. Results: The main identified families were Beijing (28.1%) and Haarlem (16.8%) while 34.8% of isolates were in the heterogeneous L4-unclassified group. Although the Beijing family was the most prevalent (61.5%) among MDR-TB cases, it accounted for only 2% of DS isolates. Among foreign-born patients, a higher ratio of MDR isolates were observed when compared with those who Poland-born (64.3% vs. 40%). Furthermore, all patients from the Former Soviet Union (FSU) countries were infected with MDR-TB. Conclusions: Whereas DS M. tuberculosis population in Poland is dominated by L4 isolates, MDR isolates are mostly of the Beijing genotype. The rise in the prevalence of the Beijing isolates in Poland, coupled with high proportion of the Beijing genotype among foreign-born TB patients may reflect an ongoing transmission of this family, imported to Poland mainly from FSU countries.